The Effectiveness of Storytelling in Improving Speaking Skills of Junior High School Students - Pakpahan, Femi; Sadira, Lulu; Syifah, Naurah; Jodi , Setiawan; Panjaitan, Erdo; Meisuri, Wiwiek (Yayasan Sagita Akademia Maju, 2025)
Speaking is one of the most challenging skills for junior high school students, as it requires fluency, pronunciation accuracy, confidence, and expressive communication. Many students struggle with speaking English due to limited exposure, fear of making mistakes, and lack of engaging learning methods. This study aims to analyze the effectiveness of storytelling in improving the speaking skills of eighth-grade students, particularly in terms of pronunciation, fluency, confidence, and expressive delivery. Using a qualitative research approach, this study involved 20 eighth-grade students with limited English-speaking experience who participated in a five-day storytelling program, where they practiced speaking in small groups guided by tutors. Data were collected through pre- and postobservations, video recordings, and student reflections. The results indicate that storytelling significantly improved students’ speaking abilities, as they became more fluent, confident, and expressive in their storytelling performances. Initially, students exhibited hesitation and struggled with pronunciation, but by the final session, they demonstrated greater clarity, natural fluency, and expressive body language. Peer collaboration and tutor support played a crucial role in fostering students' engagement and reducing anxiety. Despite some early challenges, students ultimately found storytelling enjoyable and beneficial for their speaking development. These findings suggest that storytelling should be integrated into English learning as an interactive and effective method to improve students' oral communication skills, with further research needed to explore its long-term impact and its effectiveness compared to other speaking-based teaching methods.